The challenges of collaboration for academic and community partners in a research partnership: Points to consider - Friedman Ross, Lainie; Loup, Allan; Nelson, Robert M.; Botkin, Jeffrey R.; Lost, Rhonda; Smith, George R. Jr.; Gehlert, Sarah (Journal of Empirical Research on Human Research Ethics, 2010)
« The philosophical underpinning of Community-Engaged Research (CEnR) entails a collaborative partnership between academic researchers and the community. The Community-Based Participatory Research (CBPR) model is the partnership model most widely discussed in the CEnR literature and is the primary model we draw upon in this discussion of the collaboration between academic researchers and the community. In CPBR, the goal is for community partners to have equal authority and responsibility with the academic research team, and that the partners engage in respectful negotiation both before the research begins and throughout the research process to ensure that the concerns, interests, and needs of each party are addressed. The negotiation of a fair, successful, and enduring partnership requires transparency and understanding of the different assets, skills and expertise that each party brings to the project. Delineating the expectations of both parties and documenting the terms of agreement in a memorandum of understanding or similar document may be very useful. This document is structured to provide a “points- to-consider” roadmap for academic and community research partners to establish and maintain a research partnership at each stage of the research process » [Résumé original]
Keywords: 2000 à aujourd'hui; 2010-2019; groupes communautaires; orpcc; outils; pour des recherches en milieux de pratiques; périodes historiques; recherche collaborative; recherche en milieux de pratique; recherche partenariale; ressource en ligne; régions géographiques